Stochastic optimal allocation for a battery energy storage system in high renewable-penetrated distribution networks - Zhang, Changjun; Li, Zhongzhong; Ma, Lihong; Li, Sifan; Fu, Linbei; Zhou, Hang; Wang, Haisheng; Wu, Yufen (Frontiers in Energy Research, 2024)
As the penetration of renewable distributed generation (RDG) continues rising, the stochastic and intermittent nature of its output imposes great challenges on distribution networks (DNs) such as source-load mismatch and voltage fluctuations, which seriously affects the safety and reliability of the system. Thus, this paper presents a stochastic optimal allocation method for BESS in the DN with consideration of annual load growth, BESS degradation and DN operation, aiming to minimize the overall cost of DNs and harvest more renewable energy. Based on rainflow counting concept, the BESS degradation is efficiently modeled and linearized to improve the solvability. Besides, to address the uncertainties of RDG outputs and loads, a stochastic optimization method is adopted. Furthermore, considering that a large number of integer variables of BESS allocation model may cause a heavy computation burden, a feasibility pump-based solution algorithm is introduced to accelerate the solving speed. Finally, the effectiveness of the proposed BESS allocation method as well as the solution algorithm is verified on a 33-bus DN system through comparative analyses, showing high efficiency and performance.